Muscle activity and pedal force profile of triathletes during cycling to exhaustion - Diefenthaeler, F.; Coyle, E. F.; Bini, R. R.; Pivetta Carpes, F.; Vaz, M. A. (Sports Biomechanics, 2012)
The purpose of this study was to analyze pedaling cadence, pedal forces, and muscle activation of triathletes during cycling to exhaustion. Fourteen triathletes were assessed at the power output level relative to their maximal oxygen uptake (355 ± 23 W). Cadence, pedal forces, and muscle activation were analyzed during start, middle, and end test stages. Normal and tangential forces increased from the start to the end of the test (-288 ± 33 to - 352 ± 42 N and - 79 ± 45 to - 124 ± 68 N, respectively) accompanied by a decrease in cadence (96 ± 5 to 86 ± 6 rpm). Muscle activation increased from the start to the middle and the end in the gluteus maximus (27 ± 5.5% and 76 ± 9.3%) and in the vastus lateralis (13 ± 3.5% and 27 ± 4.4%), similar increase was observed from the start to the end in the rectus femoris and the vastus medialis (50 ± 9.3% and 20 ± 5.7%, respectively). Greater normal force along with enhanced activation of knee and hip extensor muscles is linked with fatigue and declines in cadence of triathletes during cycling to exhaustion.